Usando a antimatéria na medicina moderna - Machado, A. C.B. [UNESP]; Pleitez, Vicente [UNESP]; Tijero, M. C. (FapUNIFESP (SciELO), 2006)
In this paper we discuss how the existence of antimatter, one of the main concepts of modern physics, is used in modern medicine in the so-called positron emission tomography (PET). It consists of bringing about digital images of the body, which are obtained through the detection of the radiation produced in the electron-positron annihilation. Copyright by the Sociedade Brasileira de Física.
Using antimatter in modern medicine
Keywords: Anti-matter; Medical physics; PET